The Effect of Innovation on Productivity in Services: Evidence from Germany - Kraus, Laura Elisabeth (Student Undergraduate Research E-journal!, 2019)
Innovation has already been in the past an important driver for change, performance and competitive advantage. Due to the constantly changing and more complex environment through instant flow of information, it gets increasingly more important nowadays. While the manufacturing sectors applied innovation in various ways, the structural transformation entails innovation to services. However, the corresponding amount of research is scarce and its implications for organizational change and company’s productivity. Hence, this research study aims to investigate the effect of innovation on productivity in service firms in Germany. The results suggest that innovation and productivity are negatively related.